Airway epithelial type‐2 alarmin profiles: Blood eosinophil counts remain in memory. Issue 4 (6th March 2023) - Vernisse, Charlotte; Tuaillon, Edouard; Suehs, Carey; Gras, Delphine; Bedin, Anne Sophie; Charriot, Jeremy; Knabe, Lucie; Vachier, Isabelle; Chanez, Pascal; Petit, Aurélie; Bourdin, Arnaud
Abstract: Epithelial cytokines are involved in the orchestration of T1/T2 inflammatory patterns. We question the persistence of this trait in air–liquid interface (ALI) epithelial cultures and whether this local orientation can be related to systemic patterns (e.g., blood eosinophil counts [BECs]). We investigated alarmin release related to high versus low T2 phenotypes associated with chronic airway diseases. ALIs were reconstituted from 32 control, 40 chronic obstructive pulmonary disease, and 20 asthmatic patients. Interleukin‐8 (IL‐8; a T1‐cytokine), IL‐25, IL‐33, and thymic stromal lymphopoietin (T2‐alarmins) concentrations were assessed in subnatants at steady state and used to explain blood neutrophil and eosinophil counts. IL‐25 and IL‐8 levels were highest in asthma ALI‐subnatants, whereas IL‐33 was sparsely detected. Thymic stromal lymphopoietin levels were similar among groups. All asthma cell cultures were T1‐high/T2‐high, while chronic obstructive pulmonary disease and controls tended to be mixed. BECs were independently explained by both disease and in‐culture T2‐alarmin levels, irrespective of the T2‐alarmin considered. The epithelial ALI‐T2 signature was more frequently high in patients with a BEC > 300/mm 3 . Despite removal from an in vivo environment for ≥2 months, ALIs release disease‐specific cytokine "cocktails" into their subnatants, suggesting continued persistence of alarmin orientation in differentiated cell line environments. Abstract : Air–liquid interface epithelial cultures were reconstituted from severe asthmatic, COPD, and control patients. Despite removal from an in vivo environment for ≥2 months, ALI cultures released disease‐specific cytokine "cocktails" into their subnatants. Peripheral blood eosinophil counts were independently explained by both disease and in‐culture T2‐alarmin levels, irrespective of the T2‐alarmin considered.